Effect of long-term use of kinesiotape on hallux valgus angle: A double-blinded randomized controlled trial - Ahmed, Mohamed M.; Qasheesh , Mohammed; Moustafa, Mahmoud Fathi Gomaa; ELsayed , Nader I. ELsayed; Abdallah , Ahmed A E; Abdelmutilibe , Sahar M.; Youssef, Ahmed S. A. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
Hallux valgus (HV) has an impact on quality of life since it alters the mechanics of the foot and causes pain. Kinesiotape (KT) has been demonstrated to be challengeable, cost-effective tool for restoring muscle function and strength, improving range of motion, reducing discomfort, and increasing lymphatic drainage. The aim of this study was to investigate the influence of 8 weeks KT on the degree HV angle (HVA) and subsequently on pain intensity. In this double-blinded randomized controlled trial, 30 subjects with HV deformity (mean age 29.07±6.3 years) were randomly allocated to study group (A) and control group (B). Group A received KT for HV, which was replaced every 5 days for 8 weeks, along with a home regular exercise program for HV, while Group B received placebo KT replaced every 5 days and the same exercise program for HV. HVA was measured using x-ray, pain intensity was measured using visual analogue scale (VAS). Outcomes were measured before and after 8 weeks of intervention. HVA showed a significant reduction in group A (p = 0.001) for both feet in comparison to group B (p = 0.11 for right foot, p = 0.09 for left foot, while pain showed significant improvement in both groups for both feet (p = 0.001). The results revealed that KT in mobile HV is effective on improving the metatarsophalangeal joint angle, decreasing pain, and hence may has positive functional impact on subjects with HV.